A review of upper limb robot assisted therapy techniques and virtual reality applications - Habiba Abdelsalam Ibrahim; Hossam Hassan Ammar; Raafat Shalaby (Institute of Advanced Engineering and Science, 2022)
Impairments in the sensorimotor system negatively impact the ability of individuals to perform daily activities autonomously. Upper limb rehabilitation for stroke survivors and cerebral palsy (CP) children is essential to enhance independence and quality of life. Robot assisted therapy has been a bright solution in the last two decades to promote the recovery process for neurological disorders patients. Nevertheless, defining the optimum intervention of robot assisted therapy (RAT) in different cases is not clear yet. With this aim, the presented study reviewed the current literature on RAT protocols for upper limb impairments and the effects of RAT on recovery outcomes. A literature search was conducted using different search engines, reviews, and studies. This study presents an overview of fourteen robotic devices used in the rehabilitation field and seventeen clinical trials using commercially available devices during the last three years. A discussion about reaching an efficient rehabilitation process based on different aspects such as clinical setting and training modes has been introduced. This review identifies the limitations of RAT to lay the foundation for more effective neuromotor disorders rehabilitation. Finally, using virtual reality (VR) as an assisting feature in RAT improves the whole process of recovering motor functionality.